Ketamine in the effective management of chronic pain, depression, and posttraumatic stress disorder for Veterans: A meta-analysis and systematic review - Liu, Jenny J.W.; Ein, Natalie; Gervasio, Julia; Baker, Clara; Plouffe, Rachel; Wanklyn, Sonya; Burhan, Amer M.; Lau, Brenda; Abreu, Emmanuel; Wasiuta, Thomas; Nazarov, Anthony; Richardson, J. Don (Frontiers in Psychiatry, 2024)
Introduction. Ketamine has emerged as a promising treatment alternative for the management of chronic pain. Despite encouraging findings in civilian populations, and favourable results from trials examining its efficacy in military populations, there is still a dearth of information pointing to optimal specifications related to ketamine administration for pain, depression, and posttraumatic stress disorder (PTSD) in military populations. This meta-analysis and systematic review synthesized available evidence on the effectiveness, tolerability, and feasibility of ketamine in the management of chronic pain and mental health conditions in military populations. Methods. This review followed the Cochrane’s Guide for systematic reviews of interventions and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as frameworks for data collection and synthesis. Results. A total of 11 studies and 22 independent samples were retained for data analyses. Across samples, improvements in pain, depression, and PTSD outcomes were evident, with the use of ketamine leading to significant reductions, g = 1.76, SE = 0.19, 95% CI (1.39, 2.13), Z = 9.26, p < .001. These effect sizes were robust with moderate-to-large effects. In addition, the reductions in symptoms were observed in both active-duty and Veteran groups, and for different routes of ketamine administration, frequencies of ketamine administration, duration of ketamine treatments, dosage, study design, and allowance for concurrent treatments. Discussion. This review provides a preliminary synthesis of available evidence which suggests that ketamine may be a potential option for the treatment of depression, PTSD, and chronic pain in military populations. The viability of ketamine as an alternative treatment may be particularly impactful for those who are treatment resistant, experience chronic symptoms, and/or have exhausted conventional treatments. More research is warranted in order verify the findings presented in this review.